Aflatoxin M1 Determination in Traditional Küp Cheese Samples of Turkey Using Immunoaffinity Column and High-Performance Liquid Chromatography - Akın Koluaçık; Göksel Tırpancı Sivri; Binnur Kaptan (Turkish Journal of Agriculture: Food Science and Technology)
Mycotoxin occurrence in foods, especially in uncontrolled produced traditional foods causes serious health problems. In this study, traditional Küp cheese samples were collected from different part of Anatolian region in Turkey (Ankara, Nevşehir and Yozgat) and analyzed to determine Aflatoxin M1 (AFM1) level. AFM1 analysis was carried out by, immunoaffinity column (IAC) clean-up and high performance liquid chromatography (HPLC) attached with fluorescence detector (FL) The level of AFM1 in all samples was in the range of 16 and 136 ng/kg which is lower than the maximum tolerance limit of the Turkish Codex Regulations (250 ng/kg). The levels of contamination indicated that more detailed and continuous monitoring is required to increase the public health conscious and reduce consumers’ exposure to AFM1.